Information adoption on social Media: How does it affect travel intention? Lessons from West Java - Rafdinal, Wahyu; Setiawati, Lina; Rachman, Annisa (Politeknik Negeri Bandung, 2022)
The ability of social media in today's digital age has been significantly developed because it has become a very important communication tool to connect with others or to know good information about products or services. One of the products that consumers adopt on social media is travel products. But information about tourist destinations on social media is not enough to be adopted by consumers to visit intention. Thus, this study aims to identify the influence of user-generated content (UGC) on social media using the information adoption model through argument quality, source credibility, perceived usefulness, and information adoption in increasing travel intention to the tourist destination in West Java. This research has conducted by accepting travel information related to social media using a sample of 404 respondents. The survey was conducted using online questionnaires and processed using the SmartPLS application for testing models and hypotheses. The results of this study showed that the entire relationship of variables showed positive results to travel intention. Information from social media through the quality of information and credibility of information plays a significant role in influencing travel intention.